A phase II trial of RCHOP followed by radioimmunotherapy for early stage (stages I/II) diffuse large B‐cell non‐Hodgkin lymphoma: ECOG3402. (14th May 2015) - Witzig, Thomas E.; Hong, Fangxin; Micallef, Ivana N.; Gascoyne, Randy D.; Dogan, Ahmet; Wagner, Henry; Kahl, Brad S.; Advani, Ranjana H.; Horning, Sandra J.
Summary Patients with early stage diffuse large B‐cell lymphoma (DLBCL) receive RCHOP (rituximab cyclophosphamide, doxorubicin, vincristine, prednisone) alone or with involved field radiotherapy (IFRT). Anti‐CD20 radioimmunotherapy (RIT) delivers radiation to microscopic sites outside of known disease. This phase II study aimed to achieve a functional complete response (CR) rate of ≥75% to RCHOP and 90Yttrium‐ibritumomab tiuxetan RIT. Patients with stages I/II DLBCL received 4–6 cycles of RCHOP followed by RIT [14·8 MBq/kg (0·4 mCi/kg)]; patients with positron emission tomographypositive sites of disease after RCHOP/RIT received 30 Gy IFRT. Of the 62 patients enrolled; 53 were eligible. 42% (22/53) had stage I/IE; 58% (31/53) stage II/IIE. After RCHOP, 79% (42/53) were in CR/unconfirmed CR. Forty‐eight patients proceeded to RIT. One partial responder after RIT received IFRT and achieved a CR. The best response after RCHOP + RIT in all 53 patients was a functional CR rate of 89% (47/53; 95% confidence interval: 77–96%). With a median follow‐up of 5·9 years, 7 (13%) patients have progressed and 4 (8%) have died (2 with DLBCL). At 5 years, 78% of patients remain in remission and 94% are alive. Chemoimmunotherapy and RIT is an active regimen for early stage DLBCL patients. Eighty‐nine percent of patients achieved functional CR without the requirement of IFRT. This regimen is worthy of further study for early stage DLBCL in a phase III trial.